Penguatan Transparansi dan Akuntabilitas pada Badan Usaha Milik Kampung (BUMK) Ono Harjo Melalui Program Pendampingan Administratif dan Digitalisasi Laporan Keuangan - Zedriansyah; Pratama, Rico Ferdian; Az Zahra, Syifa Aini; Amini, Aisyah (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
This community engagement activity aims to strengthen the capacity of Village-Owned Enterprises (BUMDes) Ono Harjo village, administrators in financial accountability and transparency. Common problems faced by BUMDes include weak financial recording systems, the absence of standard operating procedures (SOP), and minimal use of digital tools. The program used a participatory and educational approach, including initial assessments, basic bookkeeping training, introduction to digital applications, and financial reporting assistance. The results indicate an increased understanding among BUMDes managers in transaction recording, financial reporting, and the importance of having an SOP. Additionally, a standardized SOP and business cycle document based on the latest regulations was successfully prepared and adopted. This initiative is expected to promote more professional, transparent, and trusted BUMDes financial management.